Predicting High-Magnitiude, Low-Frequency Crop Losses Using Machine Learning: An Application to Cereal Crops in Ethiopia - Warner, James (2019)
James Warner WEBINAR Using Satellite Imagery for Early Warning of Productivity Constraints Organized by the Food Security Portal (FSP) OCT 31, 2019 - 11:00 AM TO 12:30 PM EDT